KESADARAN EMOSIONAL DAN KESEIMBANGAN MENTAL DALAM MEMBENTUK KEPRIBADIAN HUMANIS PESERTA DIDIK - Enik Zulaikah; Maftukhin Maftukhin; Akhmad Rizqon Khamami (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to analyze the role of emotional awareness and mental balance in shaping the humanistic personality of students who are empathetic, tolerant, and have character. The research method used isSystematic Literature Review(SLR) by reviewing relevant scientific articles published in the last ten years through international and national academic databases. The results of the study indicate that emotional awareness contributes to improving students' self-control, empathy, and social skills, while mental balance supports psychological stability and readiness to face academic and social pressures. The discussion emphasizes the importance of integrating these two aspects in an education system that emphasizes not only cognitive achievements but also affective and psychosocial dimensions. In conclusion, strengthening emotional awareness and mental balance is an effective strategy in forming a humanistic generation capable of living harmoniously in a global society.